PENGELOLAAN SUAKA MARGASATWA BUKIT RIMBANG BUKIT BALING DI KABUPATEN KAMPAR PROVINSI RIAU - Frengki Asbi; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is a study to describe the management of the Bukit Rimbang Bukit Baling conservation area in Kampar Regency, Riau Province. Conservation areas are natural conservation areas for the purpose of collecting natural and artificial plants and animals of the original and non-native species, which are utilized for the benefit of research, science, education, supporting cultivation, culture, tourism and recreation. Based on field observations and data obtained, the problems that occur are Bukit Rimbang Bukit Baling has not been properly managed by the Riau Natural Resources Conservation Center (BBKSDA) as the responsible party, because there are still forest damages committed by those who not responsible. The purpose of this study was to determine the management of Bukit Rimbang Bukit Baling natural resources in Kampar Regency, Riau Province. The concept of the theory used is a management function that starts from planning, organizing, implementing and monitoring. This research uses qualitative research methods with descriptive data analysis. In collecting data the author uses interview, observation and documentation techniques. The results of this study conclude that the management carried out by the Center for Natural Resources Conservation (BBKSDA) is still in the category of not optimal. There are still shortcomings in planning, organizing, implementing and monitoring. The factors that influence BBKSDA in the management of Bukit Rimbang Bukit Baling are lack of human resources and inadequate facilities and infrastructure to carry out management activities.Keywork: Management, Conservation, Bukit Rimbang and Bukit Baling